Study of the Characteristic Mental Development Features of Primary School Students with Visçion Impairments - Synova, Ievgeniia; Tarasun, Valentina; Sasina, Iryna; Grebeniuk, Tetyana; Glushenko, Kateryna (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Severe vision impairments are an obstacle to the adequate cognitive and social development of the child. The educational response to priority problems that occur with vision disorders requires appropriate training of vision impairment specialists. For this purpose, they need basic knowledge related to the classification of vision impairments and the main aspects of the development and education of this category of children. This study aimed to analyse the main features of educational activities of children with vision impairments using special diagnostic methods and to search for effective methods for correcting the cognitive activity of children with vision impairments. During the study, an experiment was conducted with children with vision impairments (15 children). To conduct the experiment, the study used methods proposed by V.V. Tarasun and adapted them to the contingent of children with vision impairments. In particular, the following methods: the method of motivational preferences "Three wishes", the method of "Memorising 10 words", and the method of "What, why, how". The depth and time of vision impairment are considered as a primary defect, which has corresponding secondary consequences and requires corrective action under the guidance of an experienced vision impairment specialist.